DIFFERENCES OF THE LATVIAN POPULATION PERCEPTIONS AND MEMORIES OF THE DAILY ACTIVITIES OVER 30 YEARS - Ulmane, Zane; Šneidere, Kristīne; Upesleja, Gatis; Stepens, Ainārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Regular physical activity helps to improve physical and mental functions as well as reverse some effects of chronic disease to keep older people mobile and independent (McPhee et al., 2016). However, physical activity with aerobic load elements could be a contributing factor to aging (Prakash, Voss, Erickson, & Kramer, 2015). Epidemiological studies have shown that the intensity of daily physical activity might have an important role to maintain life-long cognition (Kimura, Yasunaga, & Wang, 2013). The aim is to identify differences Latvian time use from the retrospective surveying primary data from Total Life-span Physical Activity questionnaire and tertiary data from 1979 published data on population time use and trends (Eglite, Svikis, & Zarina, 1979). Methods: The primary data of daily activities was from April to December 2019 obtained from the retrospective questionnaire “Total Lifespan Physical Activity questionnaire” (Ulmane, Šneidere, & Stepens, 2019) and tertiary data were used from 1979 published data on population time use and trends (Eglite, Svikis, & Zarina, 1979). The data were adjusted to six physical activity categories to be comparable - Work/education, physiological needs, Transportation, Leisure time, Household activities and Sports. Results: did not affect males and females differently in these measures, but only differences of some categories. Results show that the most differences were found in the categories – transportation, household activities, and sport. Conclusions: The study had several limitations because data from the 1979 published book (Eglite, Svikis, & Zarina, 1979) was only available in aggregate form. Together these results provide important insights into the difference between the capital city, small towns or rural areas, but 2019 study respondents were almost always from the capital city. However, in the future for more precise data analysis needed primary or secondary data.